Verification process for web design of UEWDM - Mubin, Siti Azreena; Jantan, Azrul Hazri; Abdulla, Rusli (Medwell Journals, 2017)
Web applications is getting complex and full of interaction features. In order to deal with the design interaction process issues, a suitable design modelling approach has been developed and it is called UEWDM. To conform the design modelling comprehensiveness and realistically, web expert’s verification need to be done towards the design modelling. Our contributions rely on the design modelling approach which would be able to support the interaction processes in the design development. Thus, in this study, we present the verification methods and the results indicate most of the experts agreed with the proposed design modelling.